Development Of Learning Media Using Geogebra on Class Viii Cartesian Field Material at SMP Negeri 2 Pematang Siantar - Raja Guk-guk, Ivo Mariani Gress; Simamora, Rianita; Sidabutar, Ropinus (EduMatika: Jurnal MIPA, 2023)
This research aims (1) to describe the level of validity of mathematics learning media using Geogebra on the Cartesian Plane material, (2) to assess the mastery level of teachers and the students' engagement using Geogebra on the Cartesian Plane material, and (3) to explore educators' and students' responses to the development of mathematics learning media using Geogebra on the Cartesian Plane material at SMP Negeri 2 Pematang Siantar. The research design employed is Research and Development, following the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation. Based on the material validation results, it falls into the highly valid category with an average of 60.5, situated in the interval 54.6 ? VR < 65. Similarly, media validation is deemed valid with an average of 82, falling within the interval 68 ? VR < 84. The validated learning media was then implemented in the teaching process. Data analysis revealed that the teacher's mastery level averaged 92, categorized as practical within the interval 74.8 ? PR < 92.4. Additionally, during the trial, the students' engagement level averaged 47, falling in the interval 44.2 ? P < 54.6. The effectiveness of the developed learning media is evidenced by the students' achievement in the eighth-grade class at SMP Negeri 2 Pematang Siantar. Out of 30 students, 25 students achieved a passing grade with a percentage of 83.4%, while 5 students did not pass, constituting 16.6%. The developed learning media meets practical criteria, receiving highly positive responses from students with an average response rate of 94.97% and positive feedback from teachers with an average response rate of 82%.